Refinement pathway for quality research interview guides: an 8-step process to refine a protocol for a complex multi-country humanitarian study - Lundi-Anne Omam; Kelli O’Laughlin; Tine Van Bortel; Iko Musa; Gallus Fung; Nicolas Tendongfor; Zara Wudiri; Mohammed Ngubdo Hassan; Alain Metuge; Yanu Pride; Rosalind Parkes-Ratanshi (Journal of Global Health Reports, 2023)
The protracted conflict in the North West and South West regions of Cameroon, and the North East states of Nigeria, has led to the closure of 29% and 26% of the health facilities, respectively. This has caused the displacement of over 2.21 million persons internally and 350,000 returnees in both countries. In turn, this has created a massive gap in service delivery, prompting humanitarian organisations and the government to use different models of primary health care delivery to affected communities. As part of a larger study, we developed and piloted the interview guides for the qualitative arm of the project since we found none exist for conflict-affected countries to orientate how to navigate the complexities of conducting quality qualitative research in fragile and challenging operating environments. Piloting interviews is important for the reliability of the interview guides to obtain good quality data from interviews. We present an eight-step process for piloting qualitative studies in multiple conflict-affected settings. These includes the development of interview guides, expert consultation, translation of interview guides, risk assessment/mobilisation, recruitment of participants, piloting interviews, modifying interview guides, reflecting on the process and reporting the pilot results.